Bioaccumulation and elimination of 14C-lindane by Enchytraeus albidus in artificial (OECD) and a natural soil - Amorim, Mónica João de Barros (2002)
http://www.sciencedirect.com/science/article/B6V74-46M5B4P-K/1/3a3b739c975b196cf18bd0a44065258a